Impact of Number of Prenatal Visits on Breastfeeding Practices - Aliya Nasim; Farhan Saeed; Farzana Azhar; Erum Saboohi (JLUMHS, 2023)
OBJECTIVE: To determine the impact of several prenatal visits on breastfeeding practices during the first six months of infant life. METHODOLOGY: This prospective cohort study was conducted in Darul-sehat Hospital Karachi from August 2021 to July 2022 among pregnant females (36-40 weeks of gestation) regardless of their parity. Multiple pregnancy, intrauterine fetal death and medical disorders were excluded. A Convenient Nonprobability sampling technique is used for the selection of participants. Participants were divided into three groups according to their number of prenatal visits. <4, 4-8, >8 and followed three times after childbirth to assess their breastfeeding practices. The first follow-up was done within 48 hours of delivery, the second at three months, and the third after six months of delivery. Each visit is assessed for three breastfeeding practices: exclusive, mixed, or bottle feeding. SPSS version 23 was used for analysis. RESULTS: Two hundred ten participants were interviewed. 78.6% were well-informed about breastfeeding during antenatal visits. Mean antenatal clinic visits of studied samples were 6 (6 -8).7.1% were found with less than four antenatal visits, 68.1% with 4-8 visits, and only 24.8% had more than eight antenatal clinic visits. The percentage of exclusive feeding is highest in group 3 (>8 visits) i,e; 52.3%, followed by 43% in 4-8 visits and lowest at 4.7% in < 4 antenatal clinic visits samples. CONCLUSION: More antenatal visits favorably influence BF practices regarding the commencement and continuation of breastfeeding